Community-associated Methicillin-Resistant Staphylococcus aureus (ca-MRSA) as a Pandemic Pathogen: Risk Factors and Implications for Healthcare - Schlatterer, Kathrin; Napp, Matthias; Gleich, Sabine; Monecke, Stefan; Arnold, Andreas; Kiefer-Trendelenburg, Thomas; Goering, Richard; Strommenger, Birgit; Werner, Guido; Daeschlein, Georg (Aktuelle Dermatologie, 2022)
Background A diversity of risk factors for ca-MRSA manifestations has been described so far. Up to date toxic contact dermatitis induced by plants has not been identified as one.Patients and Methods After intense skin contact with poison ivy in the US a 24-year-old Afro-American showed pronounced bullous contact dermatitis on the back of the neck and subsequently massive ca-MRSA furunculitis with proof of Panton-Valentine-leucocidin (PVL). After travelling to Germany, his German girlfriend developed a subacute ca-MRSA, PVL-positive superinfection of a mosquito bite at her lower leg. Both infections required surgical intervention.Results While the male patient displayed contact dermatitis by poison ivy, the female patient demonstrated two risk factors for ca-MRSA: contact with a ca-MRSA positive person and a predisposing skin lesion. Both cases underpin the role of ca-MRSA transmission and the potential severeness of wound infections in young and immunocompetent persons, just to be resolved by invasive intervention.Conclusions Marked and recalcitrant skin or soft tissue infections in otherwise healthy young patients require instant microbiological analysis and surgical intervention flanked by adequate antibiotic therapy. Contact dermatitis induced by plant toxins should be taken into consideration as possible risk factor for the acquisition of ca-MRSA.
Keywords: ca-MRSA; Risikofaktor; Follikulitis; Poison Ivy; Übertragung; beeinträchtigte Hautbarriere